2019
DOI: 10.1039/c9qi01099h
|View full text |Cite
|
Sign up to set email alerts
|

Novel orange-yellow-green color-tunable Bi3+-doped Ba3Y4−wLuwO9 (0 ≤ w ≤ 4) luminescent materials: site migration and photoluminescence control

Abstract: The site migration of Bi3+ induced orange-yellow-green photoluminescence control in Ba3Y4−wLuwO9 (0 ≤ w ≤ 4).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The PLE spectrum monitored at 550 nm consists of three absorption bands with prominent peaks at 257, 320, and 365 nm, which are attributed to the 1 P 1 → 1 S 0 and 3 P 1 → 1 S 0 electron transitions of Bi 3+ ion, respectively. [ 1d,32 ] In addition, the absorption spectrum of the NaLaMgWO 6 host (red curve) overlaps with the emission spectrum of the Bi 3+ ion (green curve), indicating some energy transfer…”
Section: Resultsmentioning
confidence: 99%
“…The PLE spectrum monitored at 550 nm consists of three absorption bands with prominent peaks at 257, 320, and 365 nm, which are attributed to the 1 P 1 → 1 S 0 and 3 P 1 → 1 S 0 electron transitions of Bi 3+ ion, respectively. [ 1d,32 ] In addition, the absorption spectrum of the NaLaMgWO 6 host (red curve) overlaps with the emission spectrum of the Bi 3+ ion (green curve), indicating some energy transfer…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, researchers have reported many Bi 3+ -activated phosphors, such as YTaO 4 : Bi 3+ , Ca 3 Ga 4 O 9 : Bi 3+ , SrLaZnO 3.5 : Bi 3+ , and Ba 3 Lu 4 O 9 : Bi 3+ . [21][22][23][24] They are mostly used to prepare white LEDs for daily lighting owing to their large full width at half maximum (FWHM) (≥100 nm) and suitable emission position. However, there are few reports about the narrowband, Bi 3+ -activated phosphors needed in WLED for highend display, but we can predict Bi 3+ -activated, narrow-band phosphors through the theories of traditional, narrow-band phosphors activated by rare-earth ions.…”
Section: Methodsmentioning
confidence: 99%
“…23 Impregnation of alumina matrix in eight-harness satin Nextel 610 fabric has been studied numerically in Ref. [ 24 ]. Modeling approaches used in the above work generally involved modeling the flow of a high viscosity resin through porous media and modeling the chemical reactions and volumetric changes during processing.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the photoluminescence excitation wavelength of Bi 3+ is shorter than those of rare earth Ce 3+ /Eu 2+ ions and mainly in the UV and n-UV region. Considering other types of n s 2 - n sp electron transitions including Pb 2+ , Sn 2+ , and Sb 3+ , the fwhm value generated from n s 2 - n sp electron transition is relatively larger and broader than that of the Ce 3+ /Eu 3+ ions. Besides, the Stokes shift value of n s 2 - n sp is usually larger than that of 4f-5d transition, and a larger Stokes shift value effectively avoids spectral overlap between photoluminescence excitation and emission spectra . Up until now, many previous studies reported broadband NIR emission of Bi 3+ -activated inorganic luminescent glasses, including bulk glasses, silica glasses, germanate glasses, fluoride glasses, chloride glasses, and chalcogenide glasses. These reported Bi 3+ -doped luminescent glasses can successfully achieve broadband NIR emission in the region of 800–1600 nm, and fwhm value reaches as high as 600 nm with an IQY value of 32%. Nevertheless, luminescent glasses still have some drawbacks, for example, low transmittance may largely decrease luminescence quantum yield.…”
Section: Common Nir-emitting Activators With Intrinsic Electron Trans...mentioning
confidence: 96%
“…149−153 Besides, the Stokes shift value of ns 2 -nsp is usually larger than that of 4f-5d transition, and a larger Stokes shift value effectively avoids spectral overlap between photoluminescence excitation and emission spectra. 154 Up until now, many previous studies reported broadband NIR emission of Bi 3+ -activated inorganic luminescent glasses, including bulk glasses, silica glasses, germanate glasses, fluoride glasses, chloride glasses, and chalcogenide glasses. 155−166 These reported Bi 3+ -doped luminescent glasses can successfully achieve broadband NIR emission in the region of 800−1600 nm, and fwhm value reaches as high as 600 nm with an IQY value of 32%.…”
Section: Common Nir-emitting Activators With Intrinsic Electron Trans...mentioning
confidence: 99%